KEBIJAKAN NON PENAL DALAM PENANGGULANGAN KEBAKARAN LAHAN DAN HUTAN OLEH KEPOLISIAN DAERAH RIAU BERBASIS TEKNOLOGI APLIKASI DASHBOARD LANCANG KUNING DIKAITKAN DENGAN UPAYA PENCEGAHAN TINDAK PIDANA PEMBAKARAN LAHAN DAN HUTAN - Sasli Rais; Erdianto Erdianto; Mukhlis R Mukhlis R (EKSEKUSI, 2022)
ABSTRACT Forest fires and land fires are thus far an annual problem in the province of riau, with effects not only harmful to the people of the province of Riau, even to those of neighboring countries, advanced and efficient technologies are needed to address the karhutla's growing problem in the province of Riau. It is intended to prevent and anticipate the possibilities of increasing the phenomenon of land fires and forests both by natural or otherwise by irresponsible human behavior.The study aims to know about the treatment of forest fires and land fires by the riau county police for the past time, to assess the weaknesses and overcare of the land and forest fires by the riau area police by using polite-yellow dashboard applications and to deride legal formulations using a yellow crude dashboard application to prevent land fires and forest fires in the province of Riau.The study came to the conclusion that handling of forest fires and land by the riau county police is done with a preventive and repressive approach. A preventive approach to this is by performing socialization, empowering communities and conducting carhutla's early detection patrols. Tackling land fires and forest using the yellow sass-yellow dashboard app method presents several weaknesses and advantages. As for the weakness in the development of the application, it is not as high as the operation of the personnel of the Riau area. Not all personnel use the technological advances as field reporting reporting specifically to monitor land fires and forests. Rather, it is overdone in the use of the first information information regarding location and direction of the windfall, both known to nearby accessible sources of water or gas, the three personnel budget problems that could be addressed through police-integrated systems. It will require the creation of a by-law product of both the law and the pp which features a dashboard application model as a primary and integrated facility for sustainable use in the karhutla management to be coordinated by police institutions. Keywords: forest and land fires, non-penal policies, and the yellow sassy dashboard application.